The influence of badminton on the psychological regulation of College Students - Wu, Xueqing; Li, Zhengli (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
To investigate the psychological effects of badminton on students. This study examines badminton's impact on college students' psychological regulation using mathematical statistics, a questionnaire survey, and a review of the relevant literature. The exercise Rating Scale (PARS-3) and the self-rating scale of physical and mental symptoms were used to conduct a quantitative analysis of the experimental results presented in this paper. After 12 weeks of routine instruction, the control group's performance did not change significantly. After 12 weeks of equally intense badminton instruction, the total mental health score of College Students in the experimental group was significantly lower than in the pre-test. The results after the experiment were significantly better than before the experiment. Under 12 weeks of badminton instruction, there were significant differences in the mental health of college students, and 12 weeks of badminton instruction of equal intensity positively affected mental health. Badminton can produce favorable changes in the psychological variables of students in higher vocational programs, demonstrating that it can improve the mental health of these individuals.